CONTRIBUTION AND EFFECTIVENESS OF ACADEMIC SUPERVISION OF MADRASAH SUPERVISORS ON EDUCATION - Abd Hakim (Asosiasi Dosen Perguruan Tinggi Islam, 2021)
Madrasah supervisors have a strategic role in the quality of education in Indonesia, so the contribution of school supervisors will have a significant effect on improving teacher performance, which will impact the implementation of learning in schools. This study aimed to determine the contribution and effectiveness of the academic supervision of madrasah supervisors on the quality of education and the factors that influence the contribution of madrasah supervisors to education. The research method used is literature study, using 2 data sources in the form of scientific journals and theses, searching for articles using the help of the Harzing's Publish or Perish application. The results showed that madrasah supervisors made a positive contribution to education in the form of mentoring teachers that would improve teacher performance. Factors affecting the contribution of school supervisors are the age and competence of madrasah supervisors. Academic supervision is effective if it is accompanied by good preparation by the madrasah supervisor, if the preparation is not maximal then academic supervision will be less effective. In the future, there needs to be a special education school for prospective school supervisors, so that competent school supervisors will be created.